The ‘No-Alternative Scenario’ in the Alternative Analysis of NEPA - Murari, Kalpana (European Journal of Sustainable Development, 2019)
Environmental impact assessment report is the primary document required to assess sustainable issues of any business/commercial activity, but it is most often overlooked for serious anomalies in its presentation to the public. It is most often incomplete and there is a need to review the standards of impact assessment procedures that help preserve environmental integrity among developing nations. The absence of sanctions for improper assessment of environmental, social and economic impacts of commercial activities, including extraction of natural resources by domestic and multinational corporations undermines sustainable development across the globe. The procedures in place to study various impacts of a business activity that enable access to genuine, verifiable and actionable information by the public require review and oversight by a third-party institution. The standardization of procedures and universal harmonization of enforcement and compliance regulations by nations has to become a topic for debate at various academic levels to gain importance. Essentially, EIA reports in large infrastructure projects serve as a blueprint for low carbon economies. Developing nations ignore vital provisions relating to the listing and analysis of alternatives in their attempt to meet developmental goals. Environmental protection is to maintain the ecological integrity of habitats and ecosystems. EIA reports, ultimately, aim at conserving and replenishing the reserves of natural resources. Judicial law has played an important role in highlighting the importance of alternatives in EIA. It is therefore important as how developing nations use the provision for the alternative analysis within their environmental laws. This paper will discuss EIA under the auspices of International law relating it to Sustainable Development. It shall emphasize the significance of providing alternatives in large infrastructure projects that have enviro-social impacts including transboundary effects and how the use of “no-action” alternative helps preserve and conserve a nation’s resources, reducing negative impacts Keywords: NEPA, CEQ, Impact Assessment, Alternatives Assessment, Alternatives Analysis, no-action alternative, hydropower, mega dams.